2023
DOI: 10.1371/journal.pone.0271478
|View full text |Cite
|
Sign up to set email alerts
|

Performance and characterization of phenol-formaldehyde resin with crude bio-oil by model compound method

Abstract: In order to clarify the effects of crude bio-oil for phenol-formaldehyde resin, the phenol-formaldehyde resin with bio-oil model compounds (BMPF) were prepared by model compound method. The bonding strength and aging resistance of BMPF were determined, and their microstructure and chemical bonds were also analyzed by scanning electron microscope, Fourier transform infrared spectroscopy, and nuclear magnetic resonance analysis, respectively. The results showed that the components of crude bio-oil had various de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Recent research revealed hydroquinone could increase cancer risk by damaging DNA and impairing the immune system 4 . Amino phenols are potentially hazardous and mutagenic chemicals utilized or released in the industrial, medicinal, and agriculture sectors 5 , 6 . Para-aminophenols (PAP) are also used as a raw material for producing Paracetamol, one of the most commonly made drugs globally.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research revealed hydroquinone could increase cancer risk by damaging DNA and impairing the immune system 4 . Amino phenols are potentially hazardous and mutagenic chemicals utilized or released in the industrial, medicinal, and agriculture sectors 5 , 6 . Para-aminophenols (PAP) are also used as a raw material for producing Paracetamol, one of the most commonly made drugs globally.…”
Section: Introductionmentioning
confidence: 99%